Patient-Specific Instrument Can Improve Functional and Radiographic Results during Learning Curve for Oxford Unicompartmental Knee Arthroplasty - Sanz-Ruiz, Pablo; Matas-Diez, Jose Antonio; Carbo-Laso, Esther; Perez-Mañanes, Ruben; Vaquero-Martín, Javier (The Journal of Knee Surgery, 2019)
The true value of use of patient-specific instrumentation (PSI) systems by inexperienced surgeons during their learning curve to improve the clinical and radiographic outcome of unicompartmental knee arthroplasty (UKA) has not been previously studied. Fifty patients with a mean age of 64.3 years undergoing surgery for Oxford UKA were prospectively divided into two groups. Twenty-five patients were operated on by a surgeon with no prior experience in UKA using a PSI system and the other 25 patients by an experienced surgeon using a conventional procedure. Patients were scored using joint range of motion (ROM), the Knee Society Score (KSS), the Knee Injury and Osteoarthritis Outcome Score (KOOS), and the 12-item Short-Form (SF-12) before and 3 months and 2 years after surgery. Impact of use of PSI was measured by comparing clinical and radiographic outcome, complications, and implant survival. No evidence of poorer clinical outcome was seen in any subscale of KSS, KOOS, and SF-12 for inexperienced surgeons using PSI (p = 0.45, p = 0.32, and p = 0.61, respectively). No difference was found between the two procedures in precision of radiographic alignment of components (p = 0.53). No complication occurred in any group. PSI may improve precision of component alignment during the learning curve of surgeons, thus achieving functional results similar to those of more experienced surgeons using a conventional procedure.
Keywords: patient-specific instrument; Oxford Knee; unicompartmental knee arthroplasty; learning curve